Are outsiders equally out everywhere? The economic disadvantage of outsiders in cross-national perspective. (December 2015) - Fervers, Lukas; Schwander, Hanna
Despite intense policy debate over labour market dualization, research on cross-country differences in the 'outsider penalty' is still in its infancy. In this article, we assess two explanations for cross-national variation in the disadvantages affecting temporary workers ('outsiders'), measured by the chances of regular employment and risk of unemployment: their socio-economic composition and the effect of labour market institutions (employment protection regulation and the strength of unions). Our findings suggest that variation in the outsider penalty is not caused by the socio-economic composition of the outsider group, but rather by the institutional setting of a country. Outsiders are more disadvantaged in countries with strong employment protection legislation. In contrast, strong unions do not reinforce but mitigate insider/outsider divides in at least some dimensions, a finding that adds to recent research about unions' reorientation towards mobilizing outsiders.